The effect of acupressure therapy on emesis gravidarum in pregnant women in the first trimester - Silvani, Erista; Triana Indrayani; Risza Choirunissa (Nursing and Health Sciences Journal (NHSJ), 2025)
Nausea and vomiting (emesis gravidarum) are among the most common complaints during the first trimester of pregnancy, often associated with elevated levels of human chorionic gonadotropin (hCG). Non-pharmacological interventions such as acupressure have been proposed as effective alternatives to manage these symptoms. This study aimed to evaluate the effectiveness of acupressure therapy in reducing the severity of emesis gravidarum among first-trimester pregnant women. A quasi-experimental design with a pretest-posttest control group was applied. A purposive sampling technique recruited 42 participants, divided equally into intervention (n=21) and control (n=21) groups. Acupressure therapy was administered to the intervention group at specific points, while the control group received routine antenatal care. Data were analyzed using paired t-test and independent t-test. The findings demonstrated a statistically significant reduction in the frequency and severity of nausea and vomiting in the intervention group compared to the control group (p < 0.001). Acupressure therapy effectively alleviated symptoms of emesis gravidarum during the first trimester. Acupressure therapy is a beneficial, non-pharmacological intervention for reducing emesis gravidarum in early pregnancy. This technique can be integrated into maternal health services to improve comfort and wellbeing.